(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to demonstrate the impact of the dimensions of the marketing vigilance represented by (environmental scanning, diagnostic capacity, validity and decision-making) and to attract deposits represented by (customer relationship management strategy, distribution strategy (location), promotion strategy), as the research was applied in each of Banks (Assyria International, Iraqi Middle East Investment, Business Bay, Iraqi Investment, Babel, Al Mansour Investment), and the questionnaire was adopted as a main tool for collecting data and information from a sample of (110) who are in the position (department manager, department manager, assistant Section Director, Division Officer, Unit Officer), and the statistical program (SPSS) was used. In the calculation of (the arithmetic mean, standard deviation, coefficient of variation, t-test, and simple linear regression), the research reached a number of conclusions, the most prominent of which were: 1. The environmental survey came first in terms of its importance from the viewpoint of the respondents, then it was followed by the other dimensions in order, namely (capacity Diagnostic, validity and decision-making) 2. The dimensions of attracting deposits to banks were arranged from the viewpoint of the respondents according to their degree of priority and importance in descending order (distribution strategy (location), customer relationship management strategy, promotion strategy) 3. The presence of a statistically significant effect of the variable marketing alertness in Attracting deposits to banks, and this gives an indication of the great positive impact that the dimensions of marketing vigilance play in attracting deposits to banks.